2018
DOI: 10.1177/2324709618798399
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Acute Pancreatitis Due to Very Severe Hypertriglyceridemia (>10 000 mg/dL) Successfully Resolved With Insulin Therapy Alone: A Case Report and Literature Review

Abstract: A 48-year-old male presented to the psychiatric emergency room for dysmorphic mood. He was admitted to medical service for the management of hyponatremia, which was discovered in his initial laboratory workup. After the first day of admission, he developed abdominal pain and fever, and subsequent laboratory work revealed a triglyceride level of 10 612 mg/dL (reference range = 0-194 mg/dL). Computed tomography scan of the abdomen and pelvis revealed a hypodense lesion in the pancreas surrounded by a moderate am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Our patient presented with mild acute pancreatitis. Upon reviewing other similar case reports on this triad, we noticed a milder presentation in patients with lower level of TG and severe presentation in patients with very high TG level [6-9]. There has also been a retrospective study on a large number of patients who depicted a more severe form of pancreatitis in the higher TG groups than that in the lower TG groups implying that an elevated TG level may be associated with a poor prognosis [10].…”
Section: Discussionmentioning
confidence: 69%
“…Our patient presented with mild acute pancreatitis. Upon reviewing other similar case reports on this triad, we noticed a milder presentation in patients with lower level of TG and severe presentation in patients with very high TG level [6-9]. There has also been a retrospective study on a large number of patients who depicted a more severe form of pancreatitis in the higher TG groups than that in the lower TG groups implying that an elevated TG level may be associated with a poor prognosis [10].…”
Section: Discussionmentioning
confidence: 69%
“… 1 The severity of acute pancreatitis in patients with hypertriglyceridemia is dependent on both the inflammatory response caused by pancreatitis itself, and the injury caused by lipotoxicity from triglyceride hydrolysis. 3 …”
Section: Discussionmentioning
confidence: 99%
“…1 The severity of acute pancreatitis in patients with hypertriglyceridemia is dependent on both the inflammatory response caused by pancreatitis itself, and the injury caused by lipotoxicity from triglyceride hydrolysis. 3 There are no current established guidelines for the treatment of very severe HTG-AP, although insulin, heparin, and plasmapheresis have all been used in the literature. Being in a rural hospital with no timely access to other treatment options, insulin drip was started as studies have showed, insulin is noninferior and as effective as plasmapheresis, which tends to be costly with limited access.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of Insulin therapy is another variable among reported cases; it ranges between 2-4 days. In non-diabetic patients lower doses of Insulin are usually used [7]. Although we used the lowest reported dose ; however, it was safe and effective to lower hypertriglyceridemia within two days.…”
mentioning
confidence: 82%